Prototype Set Praktikum Wireless Power Transfer (WPT) dengan teknik Magnetik Resonant Coupling - Heriansyah Heriansyah (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2021)
The use of Wireless Power Transfer (WPT) technology has great potential in life. There are 6 WPT techniques, one of them is magnetic resonant coupling. This technique has the principle of inductive coupling and resonance interaction on the coil. The working principle of this technique is the effect of magnetic induction on two coils that have the same resonant frequency so that they can transmit energy from one coil to another efficiently. The circuit used in the WPT is a series RLC with a circular flat spiral coil. The self-inductance values ​​of the 3 coils used were 20 µH, 130 µH, and 230 µH, respectively. The power efficiency at WPT increases as the self-inductance of the coil increases. Resonance frequencies for each coil are in the range of 70-80 kHz for coils with an inductance of 20 µH, 30 kHz for coils with an inductance of 130 µH, and around 20 kHz for coils with an inductance of 230 µH, respectively